Financial perfomance before and during the covid 19 pandemic on Indonesia soe Banking - Nortuah; Ekayana Sangkasari Paranita (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to analyze the financial performance of Indonesian State-Owned-Enterprise in banking sector before and during the Covid-19 pandemic. So far, state-owned banks have had superior financial performance, but the economic slowdown during the COVID-19 pandemic has hit their performance hard. Secondary data used in this study are collecting from each bank financial report. Financial performance analysis conducted towards Cash Acquisiton Ratio, Non Performing Loan, Loan to Deposit Ratio, and Return On Assets. Then each ratio is compared with the composite banking index. Furthermore, statistical descriptive analysis and paired sample t-test complete the data analysis. This study concludes that there are significant differences in state-owned banking financial performance before and during the Covid-19 pandemic, especially in the decline in Non Performing Loan.